Potential of Moringa Leaves as Raw Material for Panna Cotta to Meet The Nutritional Needs of Toddlers Indicated with Stunting: Potensi Daun Kelor Sebagai Bahan Baku Panna Cotta Untuk Memenuhi Kebutuhan Nutrisi Balita Terindikasi Stunting - Indah Permata Sari, Novi; Sulistiya, Elma; Mareni, Nunky Liontin (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2025)
Abstract Stunting is a condition of failure to grow in children aged 0-5 years. The purpose of this study was to develop a superfood dessert product for toddlers indicated as stunting with moringa leaves as the basic ingredient into Panna Cotta products. Sensory test showed significant value on texture, color and after taste. The highest protein content analysis with a value of 7.76%, carbohydrates 19.2% and fat 9.7%, even so the results of fat analysis using SPSS did not show significant differences between samples with different treatments. While the highest water content was found in samples with 40% moringa milk: 5% sugar treatment, with a result of 70.18%. The highest dietary fiber content with a value of 1.42%. Based on the results of the analysis of protein, carbohydrates, fat and fiber, which are balanced and all the necessary macronutrient components are available. Abstrak Stunting adalah kondisi gagal tumbuh pada anak usia 0-5 tahun. Tujuan Penelitian ini adalah untuk mengembangkan produk makanan super food dessert untuk balita terindikasi stunting dengan berbahan dasar daun kelor menjadi produk Panna Cotta. Pada analisis sensori parameter yang signifikan terdiri dari tekstur, warna dan after taste. Analisis kadar protein tertinggi dengan nilai 7,76%, karbohidrat 19,2% dan lemak 9,7%, meskipun begitu hasil analisis lemak menggunakan SPSS tidak menunjukan perbedaan yang signifikan antar sampel dengan perlakuan yang berbeda. Sementara kadar air tertinggi diketahui pada sampel dengan perlakuan 40% susu kelor : 5% gula, dengan hasil 70,18%. Analisis kadar serat pangan tertinggi pada perlakuan 50% susu kelor : 5% gula dengan nilai 1,42%. Berdasarkan hasil analisis protein, karbohidrat, lemak dan serat, yang seimbang serta seluruh komponen zat gizi makro yang diperlukan tersedia.